2020
DOI: 10.33828/sei.v31.i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Science, Technology, Engineering, and Mathematics Integration: Science Teachers’ Perceptions and Beliefs

Abstract: this reason, they benefit from interdisciplinary approaches that provide a holistic approach to events. Therefore, science, technology, engineering, and mathematics (STEM), which is an interdisciplinary discipline, has become very popular in science teaching in recent years. STEM is a commonly used abbreviation to indicate education or professional practice in the fields of STEM (McDonald, 2016). Moore et al. (2014) explained integrated STEM education as "an effort to combine some or all of the four discipline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…The main problems encountered in practice are the problems experienced during the implementation process, the time problem, and the lack of material. This result is in parallel with other studies (Eroğlu & Bektaş, 2016;Firat, 2020;Siew et al, 2015) in the literature. According to a systematic review study conducted by Margot and Kettler (2019), teachers identified pedagogical challenges, curriculum challenges, structural challenges, student concerns, assessments, time, and knowledge, as barriers to using STEM pedagogy in their classrooms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The main problems encountered in practice are the problems experienced during the implementation process, the time problem, and the lack of material. This result is in parallel with other studies (Eroğlu & Bektaş, 2016;Firat, 2020;Siew et al, 2015) in the literature. According to a systematic review study conducted by Margot and Kettler (2019), teachers identified pedagogical challenges, curriculum challenges, structural challenges, student concerns, assessments, time, and knowledge, as barriers to using STEM pedagogy in their classrooms.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, the inability of teachers to arrange the appropriate time and environment emerges as an administrative problem. Findings from research (Firat, 2020;Siew et al, 2015) also highlight an issue of infrastructure constraints.…”
Section: Discussionmentioning
confidence: 99%
“…This was because the STEM approach improved various kinds of skills, some of which were critical thinking, creativity, different thinking patterns, higher-order thinking, analytical thinking, problem-solving skills [5], information and communication, collaboration, and communication skills [20]. STEM learning was also used to improve 21st-century skills [4], [8]. STEM-based learning was very suitable for use in Biotechnology.…”
Section: Resultsmentioning
confidence: 99%
“…The examples are research conducted by Firat (2020), Akaygun and Aslan-Tutak (2016), Parmin and Sajidan (2019), Sumen and Calisici (2016), and Matawali et al (2019). Research by Firat (2020) in Turkey found the perspective of science teachers in Turkey is not ready to integrate Science, Engineering, Technology, and Mathematics. However, they have the confidence to do so if they are trained and accustomed to integrating the STEM curriculum.…”
Section: Introductionmentioning
confidence: 99%